Anthropological Knowledge as Universal: A Critical Analysis of Fahrenheit 451. - Ullah, Ubaid; Bukhari, Syeda Muqaddas Hameed (IJET (Indonesian Journal of English Teaching), 2024)
The current research is a critical study of Bradbury's "Fahrenheit 451" and has attempted to explain how epistemology has been made conflicting and controversial, leading to the idea of implementation of universal anthropological knowledge. It is the knowledge about human races and their collective interests and benefits. Advancing anthropological knowledge is a need of the day because a majority of the world's problems are due to books. The researcher explained that universal human knowledge will build trust, tolerance, and acceptance on the part of individuals and scholars from every culture and society around the globe. The perspective of "Ethnoepistemology" has been used as a theoretical framework in guiding and providing context to the study. "Ethnoepistemology" also decentralized the concept of one dominant center in the field of knowledge i.e. “The West knowledge”. Having a qualitative and epistemological nature, the research used "Close Reading" as a method of data analysis to highlight the hidden meanings and concepts. The study concluded that the implementing and considering anthropological knowledge as universal will regain the declined scope of academia as it is universal.